(Un)Blurred Concept of Sovereign Rights at Sea : Implementation Context - Arie Afriansyah; Dila Paruna; Rania Andiani (LAW REFORM, 2020)
The term “sovereign rights” has been used on many occasions in referring to coastal states’ actions in exploring and exploiting the ocean’s natural resources beyond their sovereign territory. Not to mention the lack of comprehension between “sovereignty” and “sovereign rights” of the general public, it appears that the last term is also lacking clear definition available for a legal basis. This clarity is crucial to give the legal certainty for states’ entitlement to conduct actions within their jurisdictions. This paper tries to clarify the legal definition of “sovereign rights” under international dan national practice. It concludes that no single universally accepted definition of sovereign rights. The explanation of rights and duties of such a definition is mostly practiced both internationally and nationally. The finding is based on the survey of the implementation of international rules, international judgments, and Indonesian court decisions.